RESULTS OF INTERNAL FIXATION SURGERY IN THE TREATMENT OF CLOSED ANKLE FRACTURES AT VIET TIEP FRIENDSHIP HOSPITAL, HAI PHONG (Vietnam Journal of Community Medicine, 2026)
Background: Ankle fractures are among the most common injuries in orthopedic trauma, accounting for approximately 10% of all fractures in adults. These injuries are typically caused by rotational forces or direct trauma and may significantly impair ankle joint function if not appropriately treated.Methods: A cross-sectional descriptive study, combining retrospective and prospective data, was conducted on 31 patients with closed medial and lateral malleolar fractures. All patients underwent open reduction and internal fixation at Viet Tiep Friendship Hospital, Hai Phong, from January 2023 to March 2026.Results: Domestic accidents were the most common cause (48.4%). Most patients (67.7%) underwent surgery within the first 24 hours after injury. According to the Weber classification, type B accounted for 48.4% and type C for 51.6%. Syndesmotic disruption was observed in 48.4% of cases. The primary fixation methods included cancellous screws for the medial malleolus (96.8%) and plate-and-screw fixation for the lateral malleolus (96.8%). The rate of good anatomical reduction after surgery was 96.8%.The proportion of patients with good AOFAS scores (54.8%)Conclusion: Open reduction and internal fixation is an effective treatment for closed ankle fractures, with a high rate of anatomical restoration and low complication rates.
Keywords: ankle fracture, internal fixation, cancellous screw, plate and screw, open reduction and internal fixation.